1988
DOI: 10.1038/bjc.1988.263
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of long-chain triglycerides and medium-chain triglycerides on weight loss and tumour size in a cachexia model

Abstract: Summary A comparison has been made between the ability of long-chain triglycerides (LCT) and mediumchain triglycerides (MCT) to prevent weight loss induced by the cachexia-inducing colon adenocarcinoma (MAC16) and to reduce tumour size. There was no difference in calorie consumption or nitrogen intake between the various groups. When compared with a normal control high carbohydrate, low fat diet, animals fed MCT showed a reduced weight loss and a marked reduction in tumour size. In contrast neither weight loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In addition to restricting glucose as fuel for tumors, the tumor suppressive effect of the ketogenic diet appears to be mediated through reduction of serum IGF-I and insulin levels via GH resistance ( 204 ). Intriguingly, a switch to a low carbohydrate diet can also prevent cachexia in patients undergoing chemotherapy, assisting in the retention of lean body mass ( 205 , 206 ). The application of low carbohydrate/high fat diets is a promising strategy not only for obesity reversal, but also as a potential treatment in conjunction with normal anti-cancer therapies.…”
Section: Energy Balance Insulin/igf-i and Cancermentioning
confidence: 99%
“…In addition to restricting glucose as fuel for tumors, the tumor suppressive effect of the ketogenic diet appears to be mediated through reduction of serum IGF-I and insulin levels via GH resistance ( 204 ). Intriguingly, a switch to a low carbohydrate diet can also prevent cachexia in patients undergoing chemotherapy, assisting in the retention of lean body mass ( 205 , 206 ). The application of low carbohydrate/high fat diets is a promising strategy not only for obesity reversal, but also as a potential treatment in conjunction with normal anti-cancer therapies.…”
Section: Energy Balance Insulin/igf-i and Cancermentioning
confidence: 99%
“…Ketone bodies can serve as an alternative energy source for those cells with normal mitochondrial function [23], [24], but not for cancer cells [25]. DER has been shown to have anti-tumor effects in a variety of cancers, including brain, prostate, mammary, pancreas, lung, gastric, and colon [14], [26], [27], [28], [29], [30], [31], [32], [33], [34]. DER produces anti-cancer effects through several metabolic pathways, including inhibition of the IGF-1/PI3K/Akt/HIF-1α pathway which is used by cancer cells to promote proliferation and angiogenesis and inhibit apoptosis [35], [36], [37], [38], [39], [40], [41], [42].…”
Section: Introductionmentioning
confidence: 99%
“…In these rats, it was noted that despite persistent ketosis, blood glucose levels were not significantly lower than in controls which were also fed ad libitum. This stability of blood glucose, independent of ketosis, was subsequently confirmed in studies in which mice were fed ad libitum on a KD [84,114,[121][122][123]130] although two studies reported a drop in blood glucose concentrations compared with the control group [116,131]. In the study of Magee et al, however, diet was presented as a liquid vegetable oil and energy intake was not monitored, allowing for the possibility that the animals underate voluntarily, in this way consuming a "caloric restricted KD" used in several experimental settings from the Seyfried lab [84,114,132], which was shown therein to be superior to the unrestricted KD in tumor growth control.…”
Section: Animal Studiesmentioning
confidence: 83%
“…While the diet had no effect on rats bearing the Walker 256 sarcoma [120], it decreased the cachectic weight loss in proportion to its fat content in mice bearing the mousespecific colon carcinoma MAC16 [121]. For the latter, they further proved an anti-cachectic effect of a ketogenic diet in which the MCTs were replaced with long chain triglycerides (LCTs), although to a somewhat lesser extent [122]. Contrary to LCTs, MCTs do not require transport in chylomicrones, but readily reach the liver where they are metabolized to yield high amounts of ketone bodies.…”
Section: Fat and Ketone Bodies: Anti-cachectic Effectsmentioning
confidence: 88%